Management of presenteeism. The effects on productivity of a food processing company - Galvão, Ana Maria (2016)
Presenteeism consists in going to work without conditions to produce, which can have a much higher impact than absenteeism on the productivity of an organisation. Presenteeism translates in both physical as psychological perturbations. It is a difficult to quantify reality, as is its translation into direct and indirect costs within the organisation. Our goal was to analyse the effects of presenteeism on the productivity of a company in the food-procession sector through a descriptive and transversal study of exploratory nature. The Stanford Presenteeism Scale SPS-6 (validated by Ferreira et al, 2010) and a semi-structured interview were used. Most of the workers referred having already gone to work feeling ill at least two days in the last year, mentioning that their health condition affected their performance, made them feel desperate and lacking pleasure from work. Management mentioned that presenteeism has a direct impact on productivity without, however, being able to quantify the true costs. Presenteeism is a reality in organisational scenarios, exceling in the educational and health sectors. We underline the importance of making organisations aware of the psychosocial risks and the importance of having healthy leaderships, work stress control and the presence of clinical psychologists and professional coaches.